IMPLEMENTATION OF LAND DISPUTE RESOLUTION THROUGH CUSTOMARY LAW IN THE ACEH TAMIANG COMMUNITY - Rahmad Daffa; Rahmad Efendi (Journal Analytica Islamica, 2025)
This study aims to determine how land dispute resolution through customary law mechanisms is implemented in the Aceh Tamiang community, identify the obstacles encountered, and formulate efforts that can be made to increase the effectiveness and legitimacy of customary law as a means of resolving agrarian conflicts. This study uses an empirical sociological approach. Data were obtained through in-depth interviews with traditional leaders, village officials, community members, as well as customary decision documents and related regulations. The results indicate that the customary law land dispute resolution mechanism in Aceh Tamiang remains effective as a means of resolving conflicts quickly, affordably, and maintaining social harmony. This mechanism is implemented in stages through mediation at the village level and formal customary deliberations led by the imam mukim. However, its implementation faces several obstacles, including normative, structural, and cultural ones. Normative obstacles arise from the weak formal legal basis for the forced execution of customary decisions. Structural obstacles include the low capacity of customary institutions, limited decision documentation, and minimal support from the local government. Meanwhile, cultural barriers are caused by shifting social values, customary plurality, and non-compliance by those with economic or political power with customary decisions. Efforts that can be made to increase the effectiveness and legitimacy of customary law include: drafting district qanuns that more specifically regulate land dispute resolution mechanisms through customary law; increasing the capacity of customary officials through training and coaching; revitalizing the cultural values of deliberation within the community through ongoing socialization; and synergy between customary and formal institutions through administrative recognition of customary decisions. Thus, strengthening the role of customary law is expected to maintain local values, reduce agrarian conflict, and support national legal pluralism.